2020
DOI: 10.1186/s12879-019-4740-6
|View full text |Cite
|
Sign up to set email alerts
|

Imported loiasis in France: a retrospective analysis of 167 cases with comparison between sub-Saharan and non sub-Saharan African patients

Abstract: Background: Imported loiasis is a rare cause of consultation at the return of stay in central Africa, which often poses difficult diagnostic and therapeutic questions to practitioners especially those who are unaccustomed to tropical medicine. These difficulties can lead to risks for the patients especially if inappropriate treatment is given. Large series of imported loiasis are scarce. Methods: We retrospectively studied the data including outcome in patients diagnosed with imported loiasis between 1993 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“… 6 The main clinical manifestations are ophthalmological signs, such as foreign-body sensation, and pain and pruritus in the eye with an occasional decrease in vision resulting from a subconjunctival or conjunctival presence of the worm. 13 Other systemic manifestations ( Figure 4 ) may include fever, fatigue, itchy legs, and a transient angioedema called Calabar swelling occurring mainly on the ankles, wrists, or face, and especially surrounding the eyes. 14 The adult worm might disappear through the upper fornix if not removed immediately after eye examination; however, adopting a facedown position may help the worm reappear in the eye.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 The main clinical manifestations are ophthalmological signs, such as foreign-body sensation, and pain and pruritus in the eye with an occasional decrease in vision resulting from a subconjunctival or conjunctival presence of the worm. 13 Other systemic manifestations ( Figure 4 ) may include fever, fatigue, itchy legs, and a transient angioedema called Calabar swelling occurring mainly on the ankles, wrists, or face, and especially surrounding the eyes. 14 The adult worm might disappear through the upper fornix if not removed immediately after eye examination; however, adopting a facedown position may help the worm reappear in the eye.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“… 15 Allergic manifestations, both cutaneous or visceral, are generally associated with worm rupture in presence of a heavy parasite load, after proper treatment, or spontaneously, although less frequently. 13 Loiasis may cause glomerulonephritis mediated by immunological injury, as occurs in other more common parasitic diseases such as malaria and schistosomiasis. In this case, a kidney biopsy may show globally sclerotic glomeruli and proteinuria from a urine test.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Nonetheless, a significant number of patients may only present eosinophilia, mild nonspecific symptoms or no symptoms at all. 3 Although it has been traditionally considered a “benign” infection, it has recently been associated with an excess mortality rate 4,5 and a broad range of vital organ involvement in patients with high microfilaremia. 2 The diagnosis is based on the visualization of microfilariae using a blood concentration technique (Ho Thi Sang method with saponin) and subsequent staining of a smear with hematoxylin, extracting blood samples at midday in view of the diurnal periodicity of microfilariae circulation in peripheral blood.…”
Section: To the Editorsmentioning
confidence: 99%
“…First-line medicine is DEC, which acts against both microfilariae and adult worms. 3 Before starting the treatment, it is compulsory to exclude onchocerciasis coinfection—in patients coming from areas where both filariasis occur—providing that DEC could cause blindness or disease exacerbation in these cases. Besides, patients with high microfilaremia (>2500/μL) are at risk of encephalopathy after DEC or ivermectin administration.…”
Section: To the Editorsmentioning
confidence: 99%
“…Mali, the Ivory Coast, and Rwanda. [1][2][3][4][5][6] Besides, imported cases have been cited around the world from expatriates who have visited endemic zones. [7][8][9][10][11] A study by the GeoSentinel Network between 1995 and 2004 reported that loiasis represents 25% of cases of imported filarial disease globally.…”
mentioning
confidence: 99%